Diboson physics with CMS detector - Svintradze, Irakli (Kansas State University, 2013)
In this dissertation, you will find a study of di-boson production in pp collision with the Compact Muon Solenoid (CMS) detector at Large Hadron Collider (LHC). A study of Z+gamma process is performed on the data collected by the CMS during 2011 and corresponding to integrated luminosity L= 5 fb[superscript]-1. The study consists of two parts: cross section measurement and setting the limits on anomalous trilinear gauge couplings (aTGC) between a Z boson and a photon. The measured cross-section of Z+gamma agrees within the uncertainties with the standard model predicted cross section at next to leading order. Having found no excess in cross section measurement, we set the 95% con fidence level (C.L.) limit on aTGC. Another study discussed is a study of a low-scale walking Technicolor model with rho[subscript]T and a[subscript]T production in the fully leptonic fi nal state at 95% C.L. in proton-proton collisions at center of mass energy 10 TeV scenario using Monte Carlo simulation. We conclude that such processes can be excluded with 366 pb[superscript]-1 of data for rho[superscript]T masses up to 400 GeV and the observation would require 2.8 fb[superscript]-1 of data with 5 sigma precision.
Keywords: Particle physics; Z+gamma cross section measurement; Anomalous trilinear gauge couplings; Particle Physics (0798)